WOMEN EMPOWERMENT AND YOUTH PERCEPTION IN INDIA: A SPECIAL REFERENCE TO AGARTALA MUNICIPAL AREA - Debnath, Kalipadha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Women's empowerment has become a prominent social, political, and economic issue in India. This study examines the perceptions of youth concerning women's empowerment in India, specifically within the Agartala Municipal Area. The youth, as catalysts for change, play a crucial part in the dialogue surrounding gender equality and empowerment. Analyzing the perspectives and behaviors of the younger generation allows us to understand their views on gender roles, the efficacy of current empowerment initiatives, and their personal involvement in the cause. The study examines major topics related to women's empowerment, the attitudes of youth towards gender equality, and their participation in empowerment activities, utilizing a sample of 100 individuals, both male and female, from the Agartala Municipal Area in Tripura. The methodology encompasses surveys and interviews, aimed at gathering data to comprehend the complex nature of adolescent involvement in women's empowerment. The study continues by outlining the limitations faced and proposing recommendations for future research to address the discovered gaps in the perceptions and behaviors of children in this situation.